Valka-Valga: recomposition d’une agglomération frontalière entre Lettonie et Estonie ? - Pascal Orcier (Articulo: Journal of Urban Research, 2011)
Valka (Latvia) and Valga (Estonia) form a cross-border urban continuum of 20 000 inhabitants. The article first proposes to examine the singularity of the local cross-border configuration, within the context of national restoration, which has characterized Baltic States since 1991, and then their integration to the EU. The border is nowadays completely open, but is still part of the identity and everyday life of the city. To date the urban fabric has hardly been affected by this change of status, and obstacles still prevent the development of a more intense cross-border activity. However, economic strategies do exist to mend the urban fabric, with the help of EU funds. Can an exploitation of the border be an element of conversion of a local economy weakened by the decline of industrial and agricultural activities? The economic and demographic decline is a reality, and was formerly increased by the disadvantages brought about by the border proximity and a peripheral situation in the national territories. Can the re-united city become again an important regional center, as it used to be during the past centuries?